2011
DOI: 10.5897/ajb10.2261
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition characteristics of maize (Zea mays. L.) straw with different carbon to nitrogen (C/N) ratios under various moisture regimes

Abstract: Decomposition of maize straw incorporated into soil with various nitrogen amended carbon to nitrogen (C/N) ratios under a range of moisture was studied through a laboratory incubation trial. The experiment was set up to simulate the most suitable C/N ratio for straw carbon (C) decomposition and sequestering in the soil. The purpose of this study was to determine organic C decomposition by measuring CO 2 evolution using alkali traps. Maize straw mixed with clay loam topsoil was supplied with four initial nitrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 24 publications
0
8
0
2
Order By: Relevance
“…A C/N ratio of 18:25 seems to be most suitable for microbial activity. The retention of maize residues results in a high soil C/N ratio, which restricts the decomposition of residues and leads to net N immobilization (Abro et al 2011;Alijani et al 2012). Some reports have recommended the application of additional inorganic N to amend the C/N ratio to an appropriate level; this practice has profound effects on the decomposition of maize residues, CO 2 evolution, C mineralization, and soil properties for subsequent crops (Abro et al 2011).…”
Section: Application Of Inorganic Nmentioning
confidence: 99%
See 4 more Smart Citations
“…A C/N ratio of 18:25 seems to be most suitable for microbial activity. The retention of maize residues results in a high soil C/N ratio, which restricts the decomposition of residues and leads to net N immobilization (Abro et al 2011;Alijani et al 2012). Some reports have recommended the application of additional inorganic N to amend the C/N ratio to an appropriate level; this practice has profound effects on the decomposition of maize residues, CO 2 evolution, C mineralization, and soil properties for subsequent crops (Abro et al 2011).…”
Section: Application Of Inorganic Nmentioning
confidence: 99%
“…The retention of maize residues results in a high soil C/N ratio, which restricts the decomposition of residues and leads to net N immobilization (Abro et al 2011;Alijani et al 2012). Some reports have recommended the application of additional inorganic N to amend the C/N ratio to an appropriate level; this practice has profound effects on the decomposition of maize residues, CO 2 evolution, C mineralization, and soil properties for subsequent crops (Abro et al 2011). In China, it has been observed that maize residue retention combined with N fertilization results in increases in the SOM content, field water holding capacity, soil porosity, nutrient availability (Gong et al 2008), WUE, NUE (Yan et al 2011), grain yields (by 7.1-11.1 %), and N harvest index (by 6.2-16.7 %) compared with no N fertilizer treatment Chen 2008a, 2008b).…”
Section: Application Of Inorganic Nmentioning
confidence: 99%
See 3 more Smart Citations